2011
DOI: 10.1007/s11200-009-0489-5
|View full text |Cite
|
Sign up to set email alerts
|

Strongly magnetic soil developed on a non-magnetic rock basement: A case study from NW Bulgaria

Abstract: The enhanced magnetic susceptibility of modern soils is assumed to have several reasons including, e.g., weathering of an iron-rich geological basement, natural fires, bacterial processes and atmospheric deposition of anthropogenic particles. We report on a case where none of the above sources of magnetic enhancement is evident: a modern soil with high magnetic susceptibility over the whole soil profile, developed on nonmagnetic limestones, in an area with no industrial activities. The surface magnetic suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Previous studies indicated that the highly magnetic soils were commonly found in the soils developed on rich-in magnetite rocks, such as basalt (da Costa et al, 1999;Lu et al, 2008;Moukarika et al, 1991;Paduani et al, 2009;Rivers et al, 2004), the cause of which was the input of detrital magnetite of basalt parent material in the soil-forming processes. Grison et al (2011) reported on a specific case of strongly magnetic soil developed on weakly magnetic limestone with a near-zero magnetic susceptibility in NW Bulgaria.…”
Section: Magnetic Properties Of Highly Magnetic Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that the highly magnetic soils were commonly found in the soils developed on rich-in magnetite rocks, such as basalt (da Costa et al, 1999;Lu et al, 2008;Moukarika et al, 1991;Paduani et al, 2009;Rivers et al, 2004), the cause of which was the input of detrital magnetite of basalt parent material in the soil-forming processes. Grison et al (2011) reported on a specific case of strongly magnetic soil developed on weakly magnetic limestone with a near-zero magnetic susceptibility in NW Bulgaria.…”
Section: Magnetic Properties Of Highly Magnetic Soilsmentioning
confidence: 99%
“…Leaching and residual accumulation are understood to be the dominant pedogenic process for the soils developed on calcareous rocks. Grison et al (2011) suggested a significant role of dark concretions in the limestones, which could provide a source of iron for magnetite/maghemite formation. Mechanisms responsible for the increase of magnetic susceptibility might be mainly connected with residue accumulation of micro-iron minerals in calcareous rocks.…”
Section: Origin Of the Magnetic Mineralsmentioning
confidence: 99%
“…Many previous studies have discussed sedimentary provenance and paleoenvironmental change based on the magnetic investigation of lacustrine and marine sediments and loess/paleosol sequences (Chen et al, 1999;Hu et al, 2001;Liu et al, 2003;Hounslow and Morton, 2004;Zhang et al, 2012b). In addition, soil magnetism research has ventured into heavy metal pollution (Gautam et al, 2004;Gladysheva et al, 2007;Hu et al, 2007) and pedogenesis (Grison et al, 2011;Lu et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Carbonates deposited in marine environments often possess a much higher mean P/Fe of approximately 0.219 than that of granites with P/Fe of approximately 0.067, although the Fe content in carbonates is much lower than that of granites (Chen & Wang, 2005). This difference explains the extremely high magnetism of soils in Terra Rossa derived from carbonates (Grison et al, 2011; Lu et al, 2012) when the regional climate favors the formation of Hm. In addition, the soils derived from basalts that have a high Fe content but a lower P/Fe of approximately 0.010 (Chen & Wang, 2005) have high magnetism and frequently observed FM particle growth and transformation into Hm (Camêlo et al, 2018; de Oliveira et al, 2000; Z. F. Liu, Ma, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%